CMET-23. NATURAL HISTORY AND RISK FACTORS FOR CYSTIC FORMATION AFTER STEREOTACTIC RADIOSURGERY FOR BRAIN METASTASIS. (5th November 2018) - Alattar, Ali; Hirshman, Brian; Joshi, Rushikesh; Chen, Clark
Abstract: A comprehensive review of the literature on brain metastasis (BM) stereotactic radiosurgery (SRS) revealed no publications on the natural history or risk factors for cystic formation immediately following SRS. We aimed to address this gap in knowledge by reviewing our institutional experience. We reviewed our institutional record from 2007–2017 and identified 214 consecutive patients who underwent 1, 106 SRS for BM and had >6 months of MRI follow-up. Demographic, clinical, dosimetric, and MRI data were reviewed. Statistical analysis was accomplished with Students t-test, univariate and multivariate logistic regression. The median age was 61 (range 19–91), with a median follow-up of 424 days (range 12–2, 934 days). Eleven instances of cyst formation (0.9% of 1, 106 treated lesions) were identified at SRS-treated BM sites among nine patients. Most cysts formed within a year of initial SRS. The median interval between first SRS and first evidence of cyst formation was 218 days. Seven of the nine patients (78%) with SRS-associated cysts suffered progressive cyst expansion and neurologic decline requiring steroid treatment. Four (57%) suffered continued neurologic decline despite steroid treatment and required surgical fenestration. On univariate analysis, receipt of >4 rounds of SRS to independent locations was the only variable associated with increased risk of cyst formation (odds ratio 16.58, p= 0.001). This association remained robust after adjusting for length of follow-up (odds ratio 13.59, p=0.003). This is the first study to assess cystic formation immediately following SRS for BM. The incidence of SRS-associated cyst formation during this time frame is significantly lower than previously reported for patients who survived >3 years (0.9% versus 8–10%). Cyst formation was a rare phenomenon except in patients who underwent >4 rounds of SRS, where one in three patients suffered this complication. A high proportion (78%) of SRS-associated cysts progressively expanded and required medical or surgical treatment.